ADMISSION TO USM BACHELOR’S DEGREE AND DIPLOMA PROGRAMMES 2016/2017 - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
Universiti Sains Malaysia (USM) invites applications from qualified candidates for admission into various Bachelor’s Degree and Diploma programmes (full time/distance education) for the 2016/2017 academic year.